Pengembangan Sistem Evaluasi Pembelajaran PAUD (Studi Kasus di PAUD Seruni 05 Kota Malang) - Ardhani Dwi Kinasih; Faizatul Amalia; Bayu Priyambadha (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Evaluation System of Early Childhood Education Learning aims to determine the growth and development of students, and see the success of the lesson plan. PAUD Seruni 05 records the daily activities in general in the assessment book. So the development of each student is not recorded in detail. This is in contrast to current curriculum principles. In Curriculum 2013 there are 3 kinds of assessment, namely anecdotes, checklist and artwork. The implementation of Curriculum 2013 makes it difficult for teachers because take long time to manage many detail events for each student in a day. Therefore, the Evaluation System of Early Childhood Education is developed to facilitate the process of assessment and reporting of child development. The system implements Rational Unified Process (RUP) to allow for early risk analysis, as it is developed iteratively and incrementally. Developed gradually and able to accommodate system improvements and requirements changes in Seruni 05, but keep the project schedule stay in timeline. Unit testing and integration testing show that cyclomatic complexity â‰¤ 10. Usability testing implementing System Usability Scale (SUS) generate 84,9. Compatibility testing shows that the system can run on various smartphones Android OS version 2.3 and above.